Physical Exercise And Epigenetic: Molecular Mechanisms - Anggraeni. M, Andi Sri Dewi; Arimbi; A.Anggriani; Lesbatta, Kezia Josawel; Indriani (Universitas Negeri Semarang, 2025)
Introduction: Physical exercise is associated with an active lifestyle and offers numerous health benefits. Recent research has shown that physical exercise also influences gene expression through epigenetic mechanisms such as DNA methylation, histone modification, mRNA, and microRNA expression. These changes contribute to physiological changes and disease prevention. Objectives: This review aims to explain how physical activity can affect a person's epigenetic changes to have an impact on the prevention of chronic diseases. Method: This study is a literature review using databases such as PubMed from 2015 to 2025. Result: the review revealed that physical activity can cause epigenetic changes at the stage of DNA methylation, histone modification, RNA methylation and MiRNA. Physical activity modulates DNA methylation, affecting genes related to metabolism and immune function. Understanding this pathway is the basis for developing personalized exercise programs as interventions for the prevention and therapy of chronic diseases. Understanding this pathway is the basis for developing personalized exercise programs as interventions for the prevention and therapy of diseases. Conclusion: This study reveals the relevance of epigenetic changes to physical activity as an alternative non-pharmacological therapy because it is accompanied by a perspective in choosing the type of physical activity that suits the body's condition as a step in implementing a more precise health pattern.